FTIR Profiles, Proximate Composition, and Microbial Counts of Tauco with Sensory and Amino Acid Profiles of Ultrafiltration Fractions - Herlina, Vika Tresnadiana; Lioe, Hanifah Nuryani; Adawiyah, Dede Robiatul; Kusumaningrum, Harsi Dewantari (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Twenty-four different tauco samples, available as commercial salt-fermented soybean products in Indonesia, were investigated for their microbial counts, proximate composition, as well as FTIR profiles obtained by attenuated total reflectance-fourier transform infrared (FTIR-ATR) instrument. The total and free amino acid profiles by UHPLC, as well as sensory characteristics by taste dilution analysis (TDA) of their ultrafiltration fractions (tauco fractions with molecular weights less than 3 kDa or <3 kDa) were also revealed. The objective of this study was to comprehensively characterize the commercial tauco products in Indonesia through integrated microbial, chemical, and sensory analyses of the products and their low molecular fractions. Tauco samples had total microbes reaching 4 to 9 log CFU/g. Lactic acid bacteria (LAB), which act in the second step of fermentation, were counted at much higher levels in all samples than molds/yeasts, which are important in the first step of fermentation. FTIR profiles of tauco samples are correlated with their protein content. Functional groups correlated with the proximate composition of tauco are identified as follows: protein with carbonyl (C=O) and aliphatic hydrocarbon (C-H), fat with carbonyl (C=O), and carbohydrate with hydroxyl (O-H) groups. Umami was identified as the predominant taste of their ultrafiltration fractions. The amino acid profiles of tauco fractions <3 kDa showed relatively high residual amino acid contents, suggesting abundant peptide content. However, multivariate orthogonal projections to latent structure (OPLS) analysis showed that free amino acids, including glutamic and aspartic acids (umami), glycine and serine (sweet), and phenylalanine and tyrosine (bitter), contributed significantly to the umami characteristic of tauco. This finding shows that free amino acids could contribute to the desirable taste of tauco. This study provides a comprehensive characterization of Indonesian tauco, offering a practical scientific reference for producers to understand product variability, improve fermentation control, and enhance the consistency and value of commercial products.